The emerging role of echocardiography-based techniques in cardio-onco-hematology - Zhang, Yichan; Xie, Mingxing; Wang, Jing; Zhang, Bo (Frontiers in Oncology, 2026)
In decades, the overall survival rate for cancer patients has improved significantly with continuous advances in cancer treatment technologies. However, cancer therapeutics-related cardiac dysfunction (CTRCD) has been one of the most worrying side effects, particularly in patients with hematological malignancies (HM), affecting the quality of life for cancer survivors. Early detection and prompt treatment are of vital importance. Echocardiography-based techniques can even identify subclinical myocardial damages, which is crucial for preventing irreversible myocardial damage. Conventional transthoracic echocardiography, speckle tracking imaging, myocardial work and stress echocardiography can assess myocardial global and segmental systolic function in multiple aspects. A significant decline of those parameters indicates that cardioprotective therapy should be initiated with close monitoring. This review will discuss the diagnosis and prognostic role of echocardiography-based techniques in patients with HM.